O aborto e a caça às bruxas: as influências do Malleus Maleficarum no Código Penal Brasileiro de 1940 e suas repercussões hoje. - Valle, Thais Chianca Bessa Ribeiro do (2018)
In 1484, the Inquisitors Heinrich Kramer and James Sprenger, authorized by Pope Innocent VIII, published the manual of the Inquisition called Malleus Maleficarum, or Hammer of Sorceresses. The book reveals relationships between sexuality and power, which shape the functioning of society in accordance with maternal standards established for the female bodies, making them submissive to the patriarchal political, economic and social system. Thus, in the European society of the time, in the fifteenth century, an imaginary that remained alive in the Brazilian society of the 21st century was created. The research theorizes the relation between politics and religion, and its influences in the elaboration of the normative framework of Brazil, when narrating the historical contexts in which Malleus Maleficarum was developed, so that the influences of this in the Brazilian Penal Code of 1940 are understood, which criminalizes the practice of abortion in the Brazilian legal-political order. The present research shows how politics and religion, especially Christianity, came together to oppress the bodies of women, establishing them an ideal stereotype of the feminine, submissive and maternal, which has a direct influence on the elaboration of punitive laws of the State, especially with regard to the criminalization of abortion. Of exploratory nature, the work required intense bibliographical research to the legal dispositions in force or constant in the history of Brazil. Concepts based on human rights, individual freedoms and selfdetermination, expressed by international agreements, by feminist movements - and, as a branch of it, by Feminist Theology - are used to provide a theoretical basis for study.